Recurrent somatic loss of TNFRSF14 in classical Hodgkin lymphoma. Issue 3 (9th December 2015) - Salipante, Stephen J.; Adey, Andrew; Thomas, Anju; Lee, Choli; Liu, Yajuan J.; Kumar, Akash; Lewis, Alexandra P.; Wu, David; Fromm, Jonathan R.; Shendure, Jay
Abstract : Investigation of the genetic lesions underlying classical Hodgkin lymphoma (CHL) has been challenging due to the rarity of Hodgkin and Reed‐Sternberg (HRS) cells, the pathognomonic neoplastic cells of CHL. In an effort to catalog more comprehensively recurrent copy number alterations occurring during oncogenesis, we investigated somatic alterations involved in CHL using whole‐genome sequencing‐mediated copy number analysis of purified HRS cells. We performed low‐coverage sequencing of small numbers of intact HRS cells and paired non‐neoplastic B lymphocytes isolated by flow cytometric cell sorting from 19 primary cases, as well as two commonly used HRS‐derived cell lines (KM‐H2 and L1236). We found that HRS cells contain strikingly fewer copy number abnormalities than CHL cell lines. A subset of cases displayed nonintegral chromosomal copy number states, suggesting internal heterogeneity within the HRS cell population. Recurrent somatic copy number alterations involving known factors in CHL pathogenesis were identified ( REL, the PD‐1 pathway, and TNFAIP3 ). In eight cases (42%) we observed recurrent copy number loss of chr1:2, 352, 236‐4, 574, 271, a region containing the candidate tumor suppressor TNFRSF14 . Using flow cytometry, we demonstrated reduced TNFRSF14 expression in HRS cells from 5 of 22 additional cases (23%) and in two of three CHL cell lines. These studies suggest that TNFRSF14 dysregulation may contribute to the pathobiology of CHL in a subset of cases. © 2015 Wiley Periodicals, Inc.